APPLICATION OF 3D PRINTING TECHNOLOGY AS INNOVATION IN A MOBILE INDUSTRY - Rotondo Bagliotti, Iago; Moutin Segoria Gasparotto , Angelita (Revista Interface Tecnológica, 2021)
The 3D printing technology is increasingly popular due to the benefits it brings in its application and easy creation, it´s a device which is in the reach of people as to companies, making it possible to be applied in any industrial segment. This research seeks to present that it is possible to reduce costs, development time of a new product, especially on gaining a prototype, gaining Independence and flexibility in industrial processes. Its value is linked to its versatility. Developing a new product covers the productive capacity, uncertainties, physical properties of the product, time, costs, technical knowledge, risks, specially - in generating value for the costumer. When you use it for this purpose, big part of this risks are solved initially, through product validation it's agility of the main prototypes production. So, the goal of this scientific research is to explore process themes of developing products, emphasizing the importance of a prototype applied to 3D. And in its application, a prototype of an innovative product was developed using 3D printing technology FFF (Fused Filament Fabrication), and as a result it was possible to notice obtaining significant results, less waste of businesses resources, significantly speeding up the development, testing and changes phase. It is concluded that this this technology exists in favor of the solution creations, diversified problems and acting for the business success, with an emphasis on delivering customers value, innovation, technology advance and industrial process.
Keywords: Product Development; Prototype; 3D Printing Technology